Multiplicative degree of some dihedral groups - Rhani, N. A. (American Institute of Physics Inc., 2016)
Let G be a group and H any subgroup of G. The commutativity degree of a finite group G is defined as the probability that a pair of elements x and y, chosen randomly from a group G, commute. The concept of commutativity degree has been extended to the relative commutativity degree of a subgroup H, which is defined as the probability that a random element of a subgroup, H commutes with another random element of a group G. This research extends the concept of relative commutativity degree to the multiplicative degree of a group G, which is defined as the probability that the product of a pair of elements x, y chosen randomly from a group G, is in H. This research focuses on some dihedral groups.